ANALYSIS OF SOME RESOURCES OF ECONOMIC GROWTH IN EGYPT (1977- 2012) - Khalil, Emam (European Scientific Journal, ESJ, 2015)
Economic growth is one of the basic goals that all nations strive to achieve. This achievement can be observed in whatever economic system, regardless of the stage of progress or backwardness reached. However, this is due to its impact on the welfare of the country, the level of its citizens, and its reflection on the progress and strength of the economy. Consequently, this stems from the fact that economic growth is characterized by being the outcome of a complex and interrelated process. Many factors combine to make this process succeed. These factors are economical, social, political, and institutional factors. On the other hand, many internal and external obstacles also hamper it. Many theories have discussed about economic growth. Also, different economic schools have tried to interpret its mechanisms based on variables and factors that affect it. Some economic schools focused on external factors, while others focused on the internal factors. In addition, applied studies included a variety of variables to expand the production functions which were used as a theoretical framework for models of economic growth. Thus, this was according to the nature of the economy and the specificity of the factors that controls its performance. This study aims to analyze the real GDP in Egypt sources, during the period (1977-2012) by determining the contribution of each component of the selected economic factors towards the increase of the GDP. This is with the aim of detecting the importance of each element according to its contribution in GDP. Thus, this helps decision-makers to maximize the benefit from the active growth elements. The study also seeks to predict the size of the GDP and its components during the next four years. It is an important factor to see to how much these values will reach in the future. Subsequently, this helps in shaping the future plan in accordance with the objectives of the required growth and the available possibilities with the quest to improve it.